Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Multifunctional thermally regulated aerogels for efficient solar-driven evaporation and thermoelectric power generation - Cheng Niu; Haizhen Xue; Hanxue Sun; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Rui Jiao; An Li (Chemical Engineering Journal, 2026)

Driving workload capacity of highway tunnel entrance and exit takeover under non-driving-related tasks: a multi-dimensional information coupling method - Shuangkai Zhu; Bo Liang; Jia An Niu; Rui Su; Haonan Long; Tao Deng; Mengdie Xu (Tunnelling and Underground Space Technology, 2026)

Second-order direct analysis for the design of Hong Kong's first large-scale 3D-printed steel pavilion using wire arc additive manufacturing - Liang Chen; An-Rui Liang; Siu-Lai Chan; Derek Kwok-Leung So; Tony Sai-Kwan Siu; Si-Wei Liu (Engineering Structures, 2026)

Effects of spatial distribution of slope erosion-deposition on soil quality degradation in the Mollisol region of Northeast China - Xuesong Wang; Fenli Zheng; Rui Liang; Xinyue Yang; Shuaihao Mo; Xiaobing An (Soil and Tillage Research, 2026)

Dendritic mesoporous silica-confined phase-change composites in a sodium alginate aerogel for stable solar-driven water evaporation and energy harvesting - Cheng Niu; Yanju Jing; Rui Jiao; Zhaoqi Zhu; Hanxue Sun; Weidong Liang; Jiyan Li; An Li (Chemical Engineering Journal, 2026)

Novel green ternary deep eutectic solvents for efficient extraction of nitrogen compounds from oil - Yingying Zuo; Rui Zhou; Xiaohang Yang; Jian Wang; Xu Liu; Yushan Li; Zhengqi Liang; Boxing An; Fengjuan Niu (Journal of Environmental Chemical Engineering, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Multi-factor optimization of coaxial borehole heat exchanger based on Taguchi and matrix method - Shimin Wang; Pengtao Wang; Jian'an Wang; Rui Liang; Jie Zhang; Ke Zhang; Jian Liu; Xingchen Lu; Shaoqiang Sui; Shengshan Bi (Geothermics, 2025)

Encapsulation of phase change materials in conjugated microporous polymers hollow microspheres for continuous solar-driven seawater desalination - Yanju Jing; Yong Long; Yiwan Si; Jiyan Li; Hanxue Sun; Rui Jiao; Zhaoqi Zhu; Weidong Liang; An Li (Chemical Engineering Journal, 2025)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Improved seed yield and phosphorus accumulation in soybean are associated with the enhanced root exudates in south-west China - Hong-Lan Zhang; Nian Liang; Rui Dong; Chang-An Liu; Chun-Ling Hao; Kadambot H. M. Siddique; Jin He (Plant and Soil, 2024)

Development characteristics and failure modes of reactivated ancient landslides in the Sichuan–Tibet transportation corridor, China - Rui-an Wu; Yong-shuang Zhang; Chang-bao Guo; San-shao Ren; Xin Yao; Xiao-yi Liu; Zhi-hua Yang; Guo-liang Du (Journal of Mountain Science, 2023)

Efficient numerical implementation for nonlinear analysis of pile-supported structures during soil liquefaction through adaptive pile element formulations - Weihang Ouyang; An-Rui Liang; Si-Wei Liu (Soil Dynamics and Earthquake Engineering, 2023)

Efficient antibiotic wastewater treatment via interfacial water evaporation based soot-coated conjugated microporous polymer hollow microspheres - Wenwen Luo; Meichen Liu; Rui Jiao; Yunjia Wang; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Hanxue Sun; An Li (Chemical Engineering Journal, 2023)

Occurrence, distribution and risk assessment of polycyclic aromatic hydrocarbons in soils around main water source areas of Beijing, China - Bin Li; Liang Zhao; Sining Zhong; Rui An; Ruoqi Ma; Xuming Xu; Qian Chen (Environmental Geochemistry and Health, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis - Xiaohan Hu; Rui Zhang; Hansi Liang; Jingnan An; Yuan Yang; Jie Huo; Zhenjiang Chen; Wei Quan; Lu Jiang; Cancan Li; Jian Li; Fang Li; et al. (Stem Cell Reviews and Reports, 2023)
In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived exosomes (HBM- exos) can alleviate NEC- associated intestinal injury, significantly reduce NEC score, and reduce systemic and ileal inflammation and NEC related brain injury during experimental NEC. However, the mode and mechanism of action of the two sources of exosomes were not identical. In vivo, the number of ileal crypts was more significantly restored after HBM-exos intervention than AFSC-exos, and in vitro, HBM-exos preferentially inhibited the inflammatory response of intestinal epithelial cells (IECs), whereas AFSC-exos preferentially regulated the migration of IECs. Mechanistically, GO and KEGG analyses revealed the different therapeutic mechanisms of AFSC-exos and HBM-exos in NEC. Taken together, our results illustrate that AFSC-exos and HBM-exos reduce the severity of experimental NEC and intestinal damage through different mechanisms, supporting the potential of cell-free or breast milk free exosome therapy for NEC. Graphical Abstract

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Roseococcus pinisoli sp. nov., lacking pufL and pufM bacteriochlorophyll a: synthesizing genes - Lei Shen; Miao-miao An; Rui-na Liang; Peng-xiao Liu; Xiang-wei He; Guo-zhu Zhao (Archives of Microbiology, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Mutations in circularly permuted GTPase family genes AtNOA1/RIF1/SVR10 and BPG2 suppress var2-mediated leaf variegation in Arabidopsis thaliana - Yafei Qi; Jun Zhao; Rui An; Juan Zhang; Shuang Liang; Jingxia Shao; Xiayan Liu; Lijun An; Fei Yu (Photosynthesis Research, 2016)

Shrubs and species identity effects on the distribution and diversity of ground-dwelling arthropods in a Gobi desert - Feng-Rui Li; Ji-Liang Liu; Chang-An Liu; Qi-Jun Liu; Rui-Xue Niu (Journal of Insect Conservation, 2013)

Genomewide analysis of the chitinase gene family in Populus trichocarpa - CONG JIANG; RUI FANG HUANG; JIA LIANG SONG; MIN REN HUANG; LI AN XU (Journal of Genetics, 2013)

Influences of shrub vegetation on distribution and diversity of a ground beetle community in a Gobi desert ecosystem - Ji-Liang Liu; Feng-Rui Li; Chang-An Liu; Qi-Jun Liu (Biodiversity and Conservation, 2012)

Mutations in isocitrate dehydrogenase 2 accelerate glioma cell migration via matrix metalloproteinase-2 and 9 - Yuejun Fu; Yali Zheng; Ke Li; Rui Huang; Shuhua Zheng; Na An; Aihua Liang (Biotechnology Letters, 2012)

A potential strategy for high-grade gliomas: combination treatment with lithium chloride and BmK CT - Yuejun Fu; Shuhua Zheng; Rui Huang; Na An; Yali Zheng; Zhiyun Zhang; Aihua Liang (Biotechnology Letters, 2012)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)